2012
DOI: 10.3389/fimmu.2012.00069
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines for Canine Leishmaniasis

Abstract: Leishmaniasis is the third most important vector-borne disease worldwide. Visceral leishmaniasis (VL) is a severe and frequently lethal protozoan disease of increasing incidence and severity due to infected human and dog migration, new geographical distribution of the insect due to global warming, coinfection with immunosuppressive diseases, and poverty. The disease is an anthroponosis in India and Central Africa and a canid zoonosis (ZVL) in the Americas, the Middle East, Central Asia, China, and the Mediterr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 154 publications
2
48
0
2
Order By: Relevance
“…Furthermore, the decrease in DTH response against leishmanial antigen was negatively correlated to the increase in liver/ body relative weight (R = −0.5003; p = 0.025) (Figure 3B). Since DTH is a strong correlate of protection and required for optimal development of resistance to VL [27-30], we may infer that the impaired DTH observed in KOB2 mice is an expression of deficient cellular immunity.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the decrease in DTH response against leishmanial antigen was negatively correlated to the increase in liver/ body relative weight (R = −0.5003; p = 0.025) (Figure 3B). Since DTH is a strong correlate of protection and required for optimal development of resistance to VL [27-30], we may infer that the impaired DTH observed in KOB2 mice is an expression of deficient cellular immunity.…”
Section: Resultsmentioning
confidence: 99%
“…Diferentes estudos apontam medidas mais eficazes que a eutanásia para o controle e prevenção da LV, como o uso de coleiras impregnadas com inseticidas, vacinação e tratamento dos cães infectados (Reithinger et al 2004, Solano-Gallego et al 2009, Maroli et al 2010, Palatnik-de-Sousa 2012, Fernandes et al 2014. Na Europa, e em todos os países onde a LV é endêmica, a eutanásia de cães soropositivos não é utilizada como medida de controle da doença e os cães infectados são rotineiramente tratados (Gradoni et al 1987, Alvar et al 1994, Solano-Gallego et al 2009, Solano-Gallego et al 2011.…”
Section: Discussão E Conclusãounclassified
“…It is composed of fusion of the three relatively conserved L. major proteins that is formulated with MPL-SE. Nonetheless, there is no single vaccine that is licensed for prophylaxis against VL in human [42]. In 2013, Guha et al demonstrated the potential of hemoglobin receptor (HbR) as a vaccine candidate against visceral leishmaniasis where they found that HbR is conserved across various strains of Leishmania and can potentially induce a complete protection against virulent Leishmania donovani infection challenges in both mice and hamsters [43].…”
Section: Vaccinationmentioning
confidence: 99%